2009
DOI: 10.1111/j.1537-2995.2008.02082.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after platelet transfusions in patients with thrombotic thrombocytopenic purpura

Abstract: Evidence for harm from PLT transfusions in patients with TTP is uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(60 citation statements)
references
References 59 publications
(173 reference statements)
2
55
0
3
Order By: Relevance
“…Another particular observation in those patients is that platelet transfusions did not apparently worsen TMA. This finding may be explained by the distinct and specific pathophysiology of cancer-associated TMA, and suggests that platelet transfusions are not a contraindication in this context, as they are for idiopathic TMA in the absence of severe bleeding [23].…”
Section: Discussionmentioning
confidence: 89%
“…Another particular observation in those patients is that platelet transfusions did not apparently worsen TMA. This finding may be explained by the distinct and specific pathophysiology of cancer-associated TMA, and suggests that platelet transfusions are not a contraindication in this context, as they are for idiopathic TMA in the absence of severe bleeding [23].…”
Section: Discussionmentioning
confidence: 89%
“…[30][31][32] A systematic review and analysis of data from the Oklahoma TTP-HUS Registry could neither rule in nor rule out adverse outcomes from platelet transfusions and concluded that there was "uncertain evidence of harm." 33 Our large data set suggests that platelets may be associated with 6 times higher odds of developing †Any CNS/gastrointestinal bleeding/genitourinary bleeding is reported as a "documented bleeding. "…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of published case reports and case series together with an analysis of our experience did not document a risk from platelet transfusions. 51 Most of our patients received a platelet transfusion. In most of these patients, the platelet transfusions were given as part of the common initial care for patients with severe thrombocytopenia and anemia, before the diagnosis of TTP was considered.…”
Section: Platelet Transfusionsmentioning
confidence: 98%